Training and Assistance on the Use of Picture and Picture Learning Media at SDN Kedopok 2 Probolinggo - Ludfi Arya Wardana; Dzaky Isyuniandri; Nur Halimah; Mamluatul Hasanah; Reza F. Setiani (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service is carried out to the teachers and students at SDN Kedopok 2 Probolinggo in the form of Picture and Picture training and mentoring. The purpose of this service was to improve the skills, teachers, student activities, and learning outcomes of fourth grade students of SD Negeri Kedopok 2 in science learning through the picture and picture type cooperative model. The implementation method of this service is planning, implementing, monitoring, and evaluation and recognition. The conclusion and result of this service is that through the picture and picture type cooperative model can improve teacher skills, student activities, and learning outcomes in science learning.